2011
DOI: 10.1186/1751-0147-53-35
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and endocrine profiles and reproductive parameters in dairy cows under grazing conditions: effect of polymorphisms in somatotropic axis genes

Abstract: BackgroundThe present study hypothesized that GH-AluI and IGF-I-SnabI polymorphisms do change the metabolic/endocrine profiles in Holstein cows during the transition period, which in turn are associated with productive and reproductive parameters.MethodsHolstein cows (Farm 1, primiparous cows, n = 110, and Farm 2, multiparous cows, n = 76) under grazing conditions were selected and GH and IGF-I genotypes were determined. Blood samples for metabolic/endocrine determinations were taken during the transition peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
2
13
0
3
Order By: Relevance
“…In the current study, allele frequencies of the SNP IGF-1 / Sna BI estimated for the UHFxNZHF group (A: 0.52, B: 0.48) as well as for the total sample (A: 0.59, B: 0.41), are in agreement with those previously published in North American (NA) [24], Polish [25], and Uruguayan [29] HF populations (A: 0.55, 0.52 and 0.60; B: 0.45, 0.48 and 0.40, respectively). On the other hand, allele frequencies in the sample of UHF cows tended to present a different distribution (A: 0.63, B: 0.37), which is similar to that (A: 0.64, B: 0.36) reported by Ge et al [23] in Angus beef cattle.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, allele frequencies of the SNP IGF-1 / Sna BI estimated for the UHFxNZHF group (A: 0.52, B: 0.48) as well as for the total sample (A: 0.59, B: 0.41), are in agreement with those previously published in North American (NA) [24], Polish [25], and Uruguayan [29] HF populations (A: 0.55, 0.52 and 0.60; B: 0.45, 0.48 and 0.40, respectively). On the other hand, allele frequencies in the sample of UHF cows tended to present a different distribution (A: 0.63, B: 0.37), which is similar to that (A: 0.64, B: 0.36) reported by Ge et al [23] in Angus beef cattle.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Siadkowska et al [25] and Bonakdar et al [26] reported associations between the AB genotype and higher percentage of milk fat and protein in Polish and Iranian HF cows, respectively. Likewise, previous studies from our group have shown that AB cows tended to yield more FCM than primiparous BB cows at early and middle lactation and than multiparous AA cows over the lactation period [29]. No other reports were found in the literature concerning the effect of the SNP IGF-1 / Sna BI on milk production traits.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Postpartum peripheral IGF-I levels are affected by breed/genotype [16] . Different genotypes can alter the endocrine and metabolic profiles of the transition dairy cow under grazing condition [17] . Several studies reported periparturient changes of IGF-I blood concentration in cattle [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the genomic DNAs were eluted in a volume of 100 毺L supplied elution buffer. The extracted DNA was diluted to a working concentration of [10][11][12][13][14][15][16][17][18][19][20] ng/毺L, and 2.4 毺L of it was used as a template in PCR.…”
Section: Introductionmentioning
confidence: 99%